Aging influences nucleolar responses to traumatic brain injury in Drosophila - Stacey A. Rimkus; Rebeccah J. Katzenberger; Barry Ganetzky; David A. Wassarman (PLoS ONE, 2025)
Traumatic brain injury (TBI) affects millions of people globally each year, yet effective treatments remain limited. A major challenge is the complexity of cellular and molecular responses to brain injury, many of which overlap with those seen in aging. A key hallmark of aging is nucleolar enlargement in brain and other tissues, reflecting increased ribosome biogenesis. Nucleolar size is regulated by the target of rapamycin (TOR) signaling pathway, which during aging is aberrantly activated. Inhibiting TOR reduces nucleolar size and extends lifespan in several model organisms. Using a Drosophila melanogaster model of closed-head TBI, we investigated whether injury influences nucleolar dynamics. Immunofluorescence microscopy of fibrillarin, a major nucleolar protein, revealed that brains of young, injured flies had substantially larger nucleoli than uninjured controls within one day of injury. Over the following weeks, the difference gradually diminished as nucleolar size increased in uninjured flies, eventually matching that of injured flies, which remained relatively stable. Additionally, heterogeneity in nucleolar size across cells became more pronounced with injury and aging. Finally, injury of older flies resulted in little or no nucleolar enlargement and even shrinkage within a few days of injury. These results suggest that TBI and aging converge on shared mechanisms that regulate nucleolar size, which may reach a maximal limit through either process. Consistent with this, mortality at 24 hours post-injury in young flies was significantly reduced by pharmacological inhibition of TOR with rapamycin or RapaLink-1, indicating that nucleolar enlargement contributes to TBI-induced damage. Overall, our results suggest that TBI accelerates the aging-associated increase in nucleolar size, implicating elevated ribosome biogenesis in TBI pathogenesis and highlighting TOR inhibition as a promising therapeutic approach.